2014
DOI: 10.2174/1389201015666140519123219
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microRNAs in Resistance to Chemotherapy and Novel Targeted Agents in Non-Small Cell Lung Cancer

Abstract: Despite recent advances in understanding the cancer signaling pathways and in developing new therapeutic strategies, non-small cell lung cancer (NSCLC) shows grim prognosis and high incidence of recurrence. Insufficient disruption of oncogenic signaling and drug resistance are the most common causes of tumor recurrence. Drug resistance, intrinsic or acquired, represents a main obstacle in NSCLC therapeutics by limiting the efficacy both of conventional chemotherapeutic compounds and new targeted agents. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 106 publications
(116 reference statements)
1
39
0
Order By: Relevance
“…28 miR-31 and miR-155 significantly inhibited the cisplatin sensitivity in non-small cell lung cancer cells by suppressing ABCB9 and Apaf-1, respectively, 29,30 while miR-451 elevated the cisplatin sensitivity of A549 cells. 31 Moreover, miR-98 sensitized cisplatin-resistant A549/DDP cells via upregulation of HMGA2.…”
Section: Discussionmentioning
confidence: 91%
“…28 miR-31 and miR-155 significantly inhibited the cisplatin sensitivity in non-small cell lung cancer cells by suppressing ABCB9 and Apaf-1, respectively, 29,30 while miR-451 elevated the cisplatin sensitivity of A549 cells. 31 Moreover, miR-98 sensitized cisplatin-resistant A549/DDP cells via upregulation of HMGA2.…”
Section: Discussionmentioning
confidence: 91%
“…However, the recent discovery of microRNA may improve the knowledge about the complex control of gene expression, and help to clarify the role of different signaling pathways, involved in oncogenesis and drug resistance, in different tumor types, including NSCLC [100].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Accumulating evidence has indicated that microRNAs (miRNAs or miRs) serve a role in a number of cancer processes, including lung cancer (8)(9)(10). The results of previous studies have demonstrated that targeting or regulating miRNAs may identify novel ways to effectively overcome lung cancer resistance and personalize lung cancer therapy (11,12).…”
Section: Introductionmentioning
confidence: 99%